Dearly closeted - Nadia Asyikin Abdul Malik (Nanyang Technological University, 2022)
“Dearly Closeted,” is a project that aims to normalise LGBTQ+ topics among closeted LGBTQ+ youths especially in the Malay Muslim community by presenting a safe space for them to feel less alienated, intimidated and more aware of future possibilities of being queer while resonating with stories and shared experiences from other LGBTQ+ Muslims from various walks of life and circumstances.